Respostas
respondido por:
2
= 48 : [9 - (5 - 2 x 4)] - 2
= 48 : [ 9 - ( 5 - 8)] - 2
= 48 : [ 9 - (-3)] - 2
= 48 : [ 9 + 3] - 2
= 48 : 12 - 2
= 4 - 2
= 2
= 48 : [ 9 - ( 5 - 8)] - 2
= 48 : [ 9 - (-3)] - 2
= 48 : [ 9 + 3] - 2
= 48 : 12 - 2
= 4 - 2
= 2
juliafofs007:
aain que booom, eu acertei !!
respondido por:
0
É expressão numérica:
48: [ 9- ( 5-2 • 4 )] - 2
48: [ 9 - (- 3 • 4 )] -2
48 : [ 9 -12 ] - 2
48 : 3 - 2
16 - 2
14
48: [ 9- ( 5-2 • 4 )] - 2
48: [ 9 - (- 3 • 4 )] -2
48 : [ 9 -12 ] - 2
48 : 3 - 2
16 - 2
14
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás